KUALITAS PELAYANAN DAN CITRA MEREK MENINGKATKAN KEPUTUSAN TINGGAL: PERAN KOLABORASI SEBAGAI VARIABEL MEDIATING - Matthew John Andreson; Parlagutan Silitonga (Jurnal Ekonomi dan Bisnis, 2024)
Collaboration is a strategy for sustainable business in all areas of business. The objective of this study is to enhance the efficacy of stay decisions through the utilization of collaboration mediators. The study population consisted of Miracle Signature Hills guests. The technique used was convenience sampling to select 250 respondents. SEM with Smart PLS software was used to analyze the data. The results showed that Service Quality has a significant impact on deciding to co-operate and decide to stay. Additionally, brand image has significant value on collaboration and retention. Collaborating also has a significant value in deciding to stay at Miracle Signature Hills. By fostering collaboration among various stakeholders, including management, employees, and guests, companies can create an environment conducive to sustainable growth and customer satisfaction. By continuing to work together, organizations will be able to continually enhance their quality of service, strengthen their brand image, and ultimately contribute to the longevity and success of their business.